2016
DOI: 10.1080/00927872.2014.999923
|View full text |Cite
|
Sign up to set email alerts
|

Splitting of Low-Rank ACM Bundles on Hypersurfaces of High Dimension

Abstract: Abstract. Let X be a smooth projective hypersurface. We derive a splitting criterion for arithmetically Cohen-Macaulay bundles over X. As an application we show that any rank 3 ACM vector bundle over X splits when dim X ≥ 7. We also derive a splitting result for rank 4 arithmetically Cohen-Macaulay bundles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Let M denote the submodule of H 2 * (X, EndE(−d)) generated by η E . We rewrite sequences ( 14) and ( 15) as (16) 0…”
Section: Proof Of Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…Let M denote the submodule of H 2 * (X, EndE(−d)) generated by η E . We rewrite sequences ( 14) and ( 15) as (16) 0…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…• In [17], it is shown that there are no rank 3 non-split ACM bundles on any smooth hypersurface in P 6 . • Partial results for rank 4 ACM bundles have been obtained in [16].…”
Section: Introductionmentioning
confidence: 99%